The m6A methylation landscape, molecular characterization and clinical relevance in prostate adenocarcinoma - Li, Chao; Peng, Dongyi; Gan, Yu; Zhou, Lei; Hou, Weibin; Wang, Bingzhi; Yuan, Peng; Xiong, Wei; Wang, Long (Frontiers in Immunology, 2023)
Despite the recent progress of therapeutic strategies in treating prostate cancer (PCa), the majority of patients still eventually relapse, experiencing dismal outcomes. Therefore, it is of utmost importance to identify novel viable targets to increase the effectiveness of treatment. The present study aimed to investigate the potential relationship between N6-methyladenosine (m6A) RNA modification and PCa development and determine its clinical relevance. Through systematic analysis of the TCGA database and other datasets, we identified a number of m6A-related genes with different expression and mutation profiles between PCa and normal tissues. Patient samples were divided into high- and low-risk groups based on the results of Least Absolute Shrinkage and Selection Operator (LASSO) Cox analysis. Subsequently, differences in biological processes and genomic characteristics of the two risk groups were determined, followed by functional enrichment analysis and gene set enrichment (GSEA) analysis. Next, we constructed the protein-protein interaction (PPI) network of differentially expressed genes between patients in high- and low-risk groups, along with the mRNA-miRNA-lncRNA network. The correlation analysis of tumor infiltrating immune cells was further conducted to reveal the differences in immune characteristics between two groups. In conclusion, this study provides novel findings that can further the understanding of the role of m6A methylation during the progression of PCa, which may facilitate the invention of targeted therapeutic drugs.